2019
DOI: 10.1055/s-0039-1685487
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Morphological Studies of the Stifle Menisci in Donkeys, Goats and Dogs

Abstract: The present work aims to provide more anatomical information on the stifle joint of the investigated species using computed tomography with gross anatomical cross-sections. The current work analyzed the stifle joint of the pelvic limbs of 12 adult donkeys, goats and dogs of both genders. The medial condyle of the femur was larger than the lateral one in the donkey, while it was smaller and lower than the lateral one in the goat and in the dog. The unsuitable femoral and tibial condyles were adapted by the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…During the dissection, it was observed that the lateral condyle of the femur was larger than the medial one, and this is similar to goat and dog, as evidenced in the study of Abumandour et al [35].…”
Section: Articular Surfacessupporting
confidence: 69%
See 1 more Smart Citation
“…During the dissection, it was observed that the lateral condyle of the femur was larger than the medial one, and this is similar to goat and dog, as evidenced in the study of Abumandour et al [35].…”
Section: Articular Surfacessupporting
confidence: 69%
“…The medial meniscus was slightly narrower and less thickened than the lateral, similar to the goat and dog, where the lateral was the largest, and more concave and thicker, contrary to the donkey, where the medial meniscus was larger than the lateral meniscus [35].…”
Section: Means Of Attachment Joint Capsule and Ligamentsmentioning
confidence: 76%
“…The gross morphology of these bones is well described in livestock with minor comparative points to the ruminants 5,7,8,12 . The gross anatomical features of these bones and their functional structure were described 1,2,4 . However, the available anatomical data about the skeletal components of zebu (Bos Taurus indicus) are scanty.…”
Section: Introductionmentioning
confidence: 99%
“…CT and MRI became widely used in veterinary practice as modern diagnostic modalities for the evaluation of multiple musculoskeletal disorders (Keane et al, 2017;Morrow et al, 2000). These techniques characterized by the entire visualization of both bone and soft tissues without overlapping or superimposing (Abumandour et al, 2019(Abumandour et al, , 2020Kraft & Gavin, 2001). Moreover, CT and MRI are characterized by high-contrast resolution, tomographic nature and three-dimensional reconstructed images which enable better differentiation of the structural anatomical relationships (Thrall, 2013).…”
Section: Introductionmentioning
confidence: 99%